(untitled) (Bangladesh Journal of Microbiology, 2016)
Present study was designed to investigate antibacterial, antidiabetic and lipid lowering effects of ethanolic leaf extract of Ipomoea aquatica (IA). The antibacterial effect of IA leaf extract was performed using agar-cup-diffusion assay against six pathogenic bacterial strains such as Klebsiella aerogenes, Escherichia coli, Staphylococcus aureus and Bacillus cereus Vibrio cholerae and Salmonella typhi. This extract has potent antibacterial effect against all six strains compared to commercially available antibiotics of cetriaxone, ciprofloxacin and ampicillin. Total of 40 Swiss Albino male mice were used for investigation of antidiabetic and lipid lowering effects and made diabetic by alloxan. 20 mice were used for oral glucose tolerance test (OGTT) and 20 mice for a week-long anti-hyperglycemic. Both groups were subdivided into four, each having 5 mice- i) the control receive only 0.5% methyl cellulose as vehicle; ii) Standard received vehicle plus metformin; iii & iv) test samples DIA 250 and DIA 500 received vehicle plus IA extract with 250 and 500 mg /kg b. wt (body weight), respectively. Lipid profile analysis was performed by estimating total cholesterol (TC), triglyceride (TG) and liver glycogen concentration on 20 mice after week-long antihyperglycemic tested mice. The glucose tolerance results showed significant (p<0.05) and improved 50.03% and 66.09% at the DIA250 and DIA500, respectively. However, IA significantly reduced (p<0.05) blood glucose level 57.89% and 69.12% at the DIA250 and DIA500, respectively for a weeklong anti-hyperglycemic activity. Both glucose tolerance and hypoglycemic effect is comparable to diabetic control group and the effect is dose dependent. In addition to anti-hyperglycemic effect, alloxan induced diabetic mice showed increase in plasma TC and TG level. After the administration of IA extract, TC and TG level were restored to near normal level which showed significant (p<0.05) results. The results of IA extract also showed significant (p<0.05) and improved liver glycogen content compared to diabetic control mice group. These results indicate that IA has antibacterial, antidiabetic and lipid lowering effects. Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 50-54